Smart Contracts: New Boundaries Between the Law and the Internet - Rubinich, Izabela Arnoldo; Lopes, Paulo Eduardo Diniz Ricaldoni; Camargos, Lais Alves; Freitas, Sergio Henriques Zandona (Journal of Applied Business and Economics, 2023)
The present study analyzes Smart Contracts and Blockchain technologies from the perspective of Contracts Right. Thus, seeks to investigate the general theory of contracts to identify whether smart contracts inserted in a blockchain meet the requirements of validity, existence, and efficiency. In addition, it seeks to use the figure of the Judge as a Service in arbitration and Ricardian Contracts to work the dynamics between traditional law and new technologies. The deductive method and scientific research were used, having as theoretical references the Brazilian Civil Code and the article, “Blockchain smart contracts and Judge as a service in Brazilian legislation.”